PENGATURAN MITIGASI BENCANA LIKUIFAKSI DALAM PERDA RTRW KABUPATEN JEMBRANA - Saputra, I Putu Bagus Darma; Sudiarta, I Ketut (Kertha Negara : Journal Ilmu Hukum, 2023)
ABSTRAK Jurnal ini memiliki tujuan untuk mengetahui pengaturan zonasi kawasan rawan bencana yang diatur dalam Perda RTRW Kabupaten Jembrana dan memberikan rekomendasi pentingnya pengaturan mitigasi bencana likuifaksi dalam Perda RTRW Kabupaten Jembrana. Metode yuridis normatif sebagai dasar metode penelitian dalam jurnal yang dikombinasikan dengan analisis peraturan perundang-undangan untuk menganalisis permasalahan hukum dalam topik bahasan. Hasil dari penelitian ini menemukan bahwa dalam Perda RTRW Kabupaten Jembrana telah mengatur zonasi kawasan rawan bencana dari beberapa jenis potensi bencana yang ada. Namun terdapat salah satu jenis potensi bencana yang belum mendapat pengaturan mitigasi dalam Perda RTRW Kabupaten Jembrana, yaitu bencana likuifaksi yang potensi terjadinya bencana ini di beberapa wilayah Kabupaten Jembrana termasuk dalam kategori risiko sedang hingga risiko tinggi. Sehingga perlu untuk menambahkan pengaturan mitigasi bencana likuifaksi dalam porses revisi Perda RTRW Kabupaten Jembrana yang terbaru. Kata Kunci: Mitigasi, Bencana Likuifaksi, Tata Ruang ABSTRACT The writing in this journal is motivated by the problem of liquefaction disaster mitigation regulation that have not been regulated in the Jembrana Regency Spatial Planning Regulation. This journal aims to find out the zoning regulation for disaster-prone areas as regulated in the Jembrana Regency Spatial Planning Regulation and provide recommendations for liquefaction disaster mitigation regulation in the Jembrana Regency Spatial Planning Regulations. The Normative Juridical Method as the basis for research methods in journals is combined with the analysis of legislation to analyze legal issues in the topic of discussion. The results is found that the Jembrana Regency Spatial Planning Regulation has regulated the zoning of disaster-prone areas from several types of potential disasters. However, there is one type of potential disaster that has not received mitigation regulation in the Jembrana Regency Spatial Planning, and that is namely the liquefaction disaster where the potential for this disaster in several areas of Jembrana Regency is included in the moderate to highrisk category. Because of that, it is necessary to add a liquefaction disaster mitigation regulation in the revision process of the latest Jembrana Regency Spatial Planning Regulation Key Words: Mitigation, Liquefaction Disaster, Spatial Planning